Literature Output on Gout: A Bibliographic Study - Manimekalai, S; Nagarajan, M (International Journal of Computer Sciences and Engineering, 2018)
This study evaluates research output on Gout carried out in different parts of the world during 1970–2017 using different bibliometric indicators. Data have been downloaded from Scopus database for the period 1970–2017 using the keywords Gout in the title and abstract fields. The study examined the pattern of growth of the output, its geographical distribution. The study Gout research output is gradually increasing. The USA, followed by the UK and German contributed the highest number of papers. The majority of the prolific institutions were located in the USA, the UK, France and Australia. The last two decades have witnessed considerable growth in research output in this field. Interestingly, the countries like the USA, the UK and Australia